Analisis Hubungan antara Usia Kehamilan, Berat Lahir Bayi, Jenis Persalinan dan Pemberian Asi dengan Kejadian Hiperbilirubinemia: ANALISIS HUBUNGAN ANTARA USIA KEHAMILAN, BERAT LAHIR BAYI, JENIS PERSALINAN DAN PEMBERIAN ASI DENGAN KEJADIAN HIPERBILIRUBIN PADA BAYI DI RUANG PERINATOLOGI RSUD DRAJAT PRAWIRANEGARA TAHUN 2020 - Husnul Khotimah; Sri Utami Subagio (Faletehan Health Journal, 2021)
Hyperbilirubinemia is one of the most common causes of infant death, caused by emergencies and complications in neonates. Many factors that influence Hyperbilirubinemia are preventable. This research aims to determine the relationship between gestational age, birth weight, type of childbirth and breastfeeding with the occurrence of hyperbilirubinemia in infants at the perinatology ward of Doctor Drajat Prawiranegara Regional General Hospital in 2020. This research is analytical with a case control design. The study population was all infants treated at the perinatology ward as many as 14,937 babies. The sample size was calculated using the odds ratio hypothesis test formula, obtained 22. The number of case samples was 22 babies and the control was 44 babies (1:2), so the total samples were 66 babies. The bivariate data analysis used chi square and the multivariate used multiple logistic regression. The research result showed there was a significant relationship between gestational age (P: 0.006), birth weight (P: 0.002), types of childbirth (P: 0.001) and breastfeeding (P: 0.000) with the occurrence of hyperbilirubinemia. The dominant factor affecting the occurrence of hyperbilirubinemia is breastfeeding. Early initiation of breastfeeding and motivating mothers with baby with hyperbilirubinemia not to panic and continue to breastfeed on demand are efforts to reduce hyperbilirubinemia.